Background parenchymal enhancement of the contralateral breast on preoperative contrast-enhanced breast MRI as a potential predictive factor for disease-free survival in triple-negative breast cancer patients - Li, Xiao-Ting; Wang, Xing; Zhu, Hai-Tao; Sun, Nan; Zhu, Hai-Bin; You, Liang; Gu, Xiao-Lei; Luo, Yao; Fan, Zhao-Qing; Sun, Ying-Shi (Frontiers in Oncology, 2025)
BackgroundBackground parenchymal enhancement (BPE) observed on dynamic contrast-enhanced (DCE) MRI of the contralateral breast is considered to be associated with survival outcomes. However, the prognostic significance of BPE in triple-negative breast cancer (TNBC) is unclear.MethodsBetween March 2017 and June 2019, 76 TNBC patients undergoing neoadjuvant therapy and subsequent surgery were included in the study. All patients underwent DCE MRI before and after neoadjuvant therapy. Radiologists graded BPE as minimum, mild, moderate, and marked. The BPE level was analyzed according to clinicopathological characteristics and MRI findings. Survival analysis was conducted for clinicopathological characteristics and MRI findings according to disease-free survival (DFS).ResultsThe mean age was 51.29 ± 9.53 years; 46 (60.5%) patients achieved pathological complete response (pCR), and 13 (17.1%) patients developed recurrence, with a median follow-up of 80 months (interquartile range: 64, 90). Dichotomous BPE (minimal/mild vs. moderate/marked) on post-NAC MRI was statistically associated with post-NAC ADC and menopausal status. Patients with BPE changing from high to low level demonstrated statistically lower recurrence rate than patients with BPE changing from low to high (P = 0.022). BPE on post-NAC MRI was in the final multivariate Cox model for DFS (HR = 6.57, minimal/mild: HR = 1), along with multifocality on post-NAC MRI (HR = 3.65, no multifocality: HR = 1) and pCR (HR = 7.27, pCR: HR = 1).ConclusionContralateral BPE and its change after neoadjuvant chemotherapy may reflect the recurrence risk in triple-negative breast cancer patients.